Pengaruh Literasi Keuangan, Ekspektasi Return, Dan Persepsi Risiko Terhadap Minat Investasi Mahasiswa Fakultas Ekonomi, Bisnis Dan Pariwisata Universitas Hindu Indonesia - Ni Wayan Tirtayanti; I Wayan Sudiana; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2025)
The foundation of all initiatives for economic expansion and recovery is investment. Among the universities with an investment gallery is UNHI. The information indicates that there are 333 clients of BEI UNHI Investment Gallery, most of whom are UNHI students. In comparison to the total number of UNHI students 3.034 this figure is quite smallThis study intends to investigate how risk, return expectations, and financial literacy are perceived by UNHI Faculty of Economics, Business, and Tourism students, and how these aspects affect their investing preferences. Students from the UNHI Faculty of Economics, Business, and Tourism's Accounting Study Program's sixth and eighth semesters made up the study's population. 181 samples were employed in this study due to the probability sampling method used in the sampling process. The analytical approach employed in this study is multiple regression analysis. The study's findings show that students at the UNHI Faculty of Business Economics are more interested in investing when they are financially literate, have higher return expectations, and perceive less risk.